Intermittent abdominal pain in IgA vasculitis - Izabel Mantovani Buscatti; Juliana Russo Simon; Vivianne Saraiva Leitao Viana; Tamima Mohamad Abou Arabi; Vitor Cavalcanti Trindade; Ana Carolina Cortez Maia; Lara Regina Cavalcante Melo; Bianca Pires Ihara; Nadia Emi Aikawa; Clovis Artur Silva (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To assess intermittent abdominal pain in IgA vasculitis patients and its relation to demographic data, clinical manifestations and treatments. Methods: A retrospective cohort study included 322 patients with IgA vasculitis (EULAR/PRINTO/PRES criteria) seen at the Pediatric Rheumatology Unit in the last 32 years. Sixteen patients were excluded due to incomplete data in medical charts. Intermittent abdominal pain was characterized by new abdominal pain after complete resolution in the first month of disease. Results: Intermittent abdominal pain was observed in 35/306 (11%) IgA vasculitis patients. The median time between first and second abdominal pain was 10 days (3-30 days). The main treatment of intermittent abdominal pain included glucocorticoid [n=26/35 (74%)] and/or ranitidine [n=22/35 (63%)]. Additional analysis showed that the frequency of intermittent purpura/petechiae (37 vs. 21%; p=0.027) and the median of purpura/petechiae duration [20 (3-90) vs. 14 (1-270) days; p=0.014] were significantly higher in IgA vasculitis patients with intermittent abdominal pain compared to those without. Gastrointestinal bleeding (49 vs. 13%; p<0.001), nephritis (71 vs. 45%; p=0.006), glucocorticoid (74 vs. 44%; p=0.001) and intravenous immunoglobulin use (6 vs. 0%; p=0.036) were also significantly higher in the former group. The frequency of ranitidine use was significantly higher in IgA vasculitis patients with intermittent abdominal pain versus without (63 vs. 28%; p<0.001), whereas the median of ranitidine duration was reduced in the former group [35 (2-90) vs. 60 (5-425) days; p=0.004]. Conclusions: Intermittent abdominal pain occurred in nearly a tenth of IgA vasculitis patients, in the first 30 days of disease, and was associated with other severe clinical features. Therefore, this study suggests that these patients should be followed strictly with clinical and laboratorial assessment, particularly during the first month of disease course.